Graduate Students’ Perceptions on their Self-Efficacy in Writing Academic Papers - kristian florensio wijaya; Concilianus Laos Mbato (ELT Worldwide: Journal of English Language Teaching, 2020)
ABSTRACTIt is notable to note here that self-efficacy needs to be ingrained strongly within graduate students to show a higher enthusiasm, efforts, and persistence in accomplishing various demanding academic writing projects. Tangibly, there are still many graduate students who lack motivation and confidence when doing academic writings. As a result, their attitudes toward writing turn into negative actions crippling their self-efficacy. This study aimed to investigate graduate students’ perceived self-efficacy in academic writings. One research problem was formulated in this study namely, how do English Education Master Students maintain their self-efficacy to accomplish their academic writings? This study employed a mixed-method harnessing classroom survey and interview questions to gather data from English Education Master Students engaging in academic writings, Sanata Dharma University, Yogyakarta. Findings from this study revealed that graduate students are able to produce more qualified academic writing products when they are motivated continuously by their lecturer. Keywords: self-efficacy, perceptions, academic writings, graduate students, mixed method